Is sex lost in translation? Linguistic and conceptual issues in the translation of sexual and reproductive health surveys. Issue 1 (2nd January 2023) - Wong, Horas T. H.; Wang, Pan; Sun, Yingli; Newman, Christy E.; Vujcich, Daniel; Vaughan, Cathy; O'Connor, Catherine C.; Jin, Defeng; Ogilvie, Erin; Zhang, Ye; Mao, Limin; Carter, Allison
Abstract: Translated questionnaires are increasingly used in population health research. Nevertheless, translation is often not conducted with the same rigour as the process of survey development in the original language. This has serious limitations and may introduce bias in question relevance and meaning. This article describes and reflects on the process of translating a large and complex sexual and reproductive health survey from English into Simplified Chinese. We interrogated assumptions embedded in taken-for-granted translation practice to locate the sociocultural origins of these assumptions. We discuss how terminology and expression related to sexual and reproductive health may lose their conceptual or linguistic significance during translation in three different ways. Firstly, meanings can be lost in the negotiation of meanings associated with linguacultural and geographical variations of terminology. Secondly, meanings can be lost in the clash between everyday and professional sexual and reproductive health discourses. Thirdly, meanings can be lost due to the design of the source questionnaire and the intended mode of survey administration. We discuss ways to help overcome the unavoidable translation challenges that arise in the process of translating English sexual and reproductive health surveys for migrants from non-English speaking backgrounds.